2018
DOI: 10.1017/s0033291718001721
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the influence of insecure attachment and parental maltreatment on the incidence and course of adult clinical depression

Abstract: Both insecure attachment and parental maltreatment contribute to an increased risk of depression with complex effects involving types of insecure attachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…This is another limitation of this study. Recent research suggested that insecure attachment and parental maltreatment increased the risk of depression [12]. Future studies should investigate the complex relationships between types of childhood maltreatment and adulthood depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is another limitation of this study. Recent research suggested that insecure attachment and parental maltreatment increased the risk of depression [12]. Future studies should investigate the complex relationships between types of childhood maltreatment and adulthood depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the influence of childhood neglect on the course of depression is considered to be independent of sociodemographic and clinical variables [11]. Recent research has suggested that an insecure attachment and parental maltreatment increased the risk of depression [12]. Therefore, childhood maltreatment has various effects on depressive symptoms in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of childhood maltreatment (CM) are one of the main contributors to mental illness (Brown, Harris, & Craig, 2019 ; Hughes et al, 2017 ). However, CM is non-specifically associated with psychiatric disorders, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The diathesis-stress model posits that psychiatric disorders result from a complex interaction of genetic predispositions and environmental factors, which gradually evolve during early development. Childhood abuse and maltreatment have been identified as major risk factors for depression and other mental illnesses in adults 13 . Although adversity and stress can exert harmful effects at any point in time during life, it is clear that early childhood and adolescence are the most sensitive periods as the central nervous system is still developing 4 .…”
Section: Introductionmentioning
confidence: 99%